La abstracción científica en Tomás de Aquino: un contrapunto entre la epistemología tomista y los textos. - Javier Cuccia, Emiliano (Scripta Mediaevalia, 2024)
This paper aims to justify the importance of an alternative approach to analyze abstractionism in Thomas Aquinas regarding the division of objects and sciences, considering that different studies so far a) show difficulties to correctly comprehend some key texts, and b) have spawned debates and disagreements among scholars to the point of preventing to generate a common doctrine on the subject.